Morphodynamics of sand mounds in shallow flows - Garcia-Hermosa, M; M. Isabel Garcia-Hermosa (2008)
Large-scale bed features are often encountered in coastal waters, and include sandbanks and spoil heaps. The morphodynamic development of such features involves complicated nonlinear interactions between the flow hydrodynamics, sediment transport, and bed profile. Numerical modelling of the morphodynamic evolution and migration of large-scale bed features is necessary in order to understand their long-term behaviour in response to changing environmental conditions. This thesis describes detailed measurements of the morphodynamics of sand mounds in unidirectional and oscillatory (tidal) flows, undertaken at the U.K. Coastal Research Facility (UKCRF). High quality data were collected, including water velocities, water levels and overhead images. The parameters tested are: three types of mound shape (circular and elliptical in plan shape, and Gaussian, cosine and triangular in cross-section); underlying fixed or mobile bed conditions; and initial crest height (submerged, surface-touching and surface-piercing). Peak flow velocities are about 0.5 m/s, the sand median grain size is 0.454 mm, and transport occurring mostly as bedload. When analysing the data, the bed contours are determined by digitising the shoreline at different water levels. From these plots, the volume, height, and centroid position of the mound are calculated. A large-scale fit method, based on a Gaussian function has been used to separate small-scale ripples from the large-scale bed structure during the evolution of an isolated sand mound or spoil heap. The bed profile after the ripples are removed is comparable to typical predictions by shallow-flow numerical solvers. The UKCRF experiments investigated the morphodynamic response of a bed mound to hydrodynamic forcing: shape changes, migration rates, volume decay and sediment transport rates. The measured migration rate and decay of a submerged sand mound in the UKCRF are found to be in satisfactory agreement with results from various theoretical models, such as the analytical solution derived by De Vriend. Numerical predictions of mound evolution by a commercial code, PISCES, are also presented for a fully submerged sand mound; the bed evolution is reasonably similar to that observed in the UKCRF. The data provided as a result of the research reported in this thesis provide insight into the behaviour of sand mounds in steady and unsteady flows at laboratory scale, and should also be useful for benchmark (validation) purposes to numerical modellers of large-scale morphodynamics.